Managing IT outsourcing performance - Solli-Sæther, Hans; Gottschalk, Petter 1950- (Premier reference source, 2010)
"This book provides a collection of methodologies and tools that can be used in managing relationships and performance of IT outsourcing" - Provided by publisher